SANKSI PIDANA TERHADAP PENYIDIK KEPOLISIAN YANG MELAKUKAN KEKERASAN DALAM PROSES PEMERIKSAAN TERSANGKA - Jose Adiguna; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2022)
In the investigation stage, investigators often commit violence that can harm the suspect, where thesuspect has rights as a human being and as a community protected by laws and regulations. In theinvestigation process, investigators do not only seek confessions from suspects, but also collectpreliminary evidence and witnesses in order to support proving the existence of a crime, whereinvestigators are given the authority to take certain actions, in order to complete the investigationprocess. But often in the investigation process, investigators use violence against suspects.Investigators who commit acts of violence against suspects may be subject to sanctions and may besubject to a Police Professional Code of Ethics. The investigation process aims to provide clarity on acriminal act that has occurred. In carrying out the investigation process, members of the policeassigned to look for evidence of a criminal act will interrogate the suspect. Article 117 (1) of theCriminal Procedure Code states that the statements of suspects or witnesses given to investigators areaccompanied without pressure from anyone or in any form.